Influence of expatriate induction management programs on expatriate performance among Non-Governmental Organizations in Sudan: a case study of Concern Worldwide’s operations in Sudan - Lubembe, E. K. (Strathmore University, 2024)
Induction program is one thing that local as well as multinational enterprises must put in place for the success of the business and in enhancing employee’s productivity. Humanitarian organizations operating in low-income countries often have to deal with unique challenges like cultural differences, limited resources, and security risks. Moreover, low-income countries also present unique socio-economic and political contexts for expatriate which needs them to be inducted to get well prepared for the working environment in the foreign country. These concerns require a different approach to effectively organize and make the expatriates induction successful. In line with these contextual and knowledge gaps, the objective of this study was to assess the influence of Induction Management programs on Expatriate performance among Non-Governmental Organization : A case study of Concern Worldwide in Sudan with specific objectives being to assess the influence of Expatriate induction training, organizational cultural induction, organizational Safety Procedures Induction and administrative induction program on Expatriate performance in Concern Worldwide in Sudan. The study was based social learning theory, reinforcement theory and a person-centered dynamic theory and how they contribute towards the development of new knowledge on the induction management program and expatriate performance. The study adopted a pragmatism philosophy the research design adopted was the correlational research design and the target population was 150 respondents. Data was collected using both interview guides and structured questionnaire. And the model used for the quantitative data was multiple regression model. While for the qualitative data a thematic analysis was adopted with the aid of NVivo. Results were presented using tables, figures and quotes/excerpts for the qualitative part. The results pinpointed a range of crucial problems for personnel with Concern Worldwide, showing a necessity for a better support system and workplace setting. Number one is the fact that the shortage of domestic psychological support services is raised as a key issue by workers during induction. The findings emphasize the importance of comprehensive induction programs. Effective expatriate induction training, cultural integration initiatives, safety procedure inductions, and administrative support are all critical components that contribute to the successful performance of expatriates in their respective roles. These results underscore the necessity for organizations to invest in well-structured induction programs to ensure their expatriates are well-prepared and supported. The study provides valuable insights into the impact of induction programs on expatriate performance, and assert that there are several limitations that should be acknowledged including, the study's sample size and scope being limited to 150 expatriates and just being specific organizations with different working environment within the regions, which in one way or the other may affect the generalizability of the findings. The study suggested a Future research to include a more diverse and larger sample to validate and extend the findings across different contexts and industries
Full - text thesis